Review of John Leslie's Universes and John Leslie's Physical cosmology and philosophy - Rolston, Holmes, 1932-2025, author; Joint Publication Board of Zygon, publisher (Colorado State University. Libraries, 1991)
John Leslie is the philosopher who has most devoted himself to the analysis of recent claims that our universe is fine-tuned for producing life. Here we have the fruit of Leslie's work across two decades, summarized in one accessible book of manageable length, seriously argued but neither overly technical nor esoteric. In a companion book, Physical Cosmology and Philosophy, Leslie couples his systematic treatment with an anthology of the principal articles in the field. Together, the two books are excellent texts for a stimulating class on cosmology.
Review of John Leslie's Universes
Review of John Leslie's Physical cosmology and philosophy
This is an electronic version of an article published in Zygon®: Journal of Religion and Science.
Keywords: cosmology; fine-tuned universe; big bang; anthropic principle; concept of nature; science; religion